Comparison of Bone Mineral Density in Thalassemia Major Patients with Healthy Controls - Mahesh Chand Meena; Alok Hemal; Mukul Satija; Shilpa Khanna Arora; Shahina Bano (Advances in Hematology)
Chronic hemoglobinopathies like thalassemia are associated with many osteopathies like osteoporosis. Methods. This observational study was carried out to compare the bone mineral density (BMD) in transfusion dependent thalassemics with that of healthy controls. Thirty-two thalassemia patients, aged 2–18 years, and 32 age and sex matched controls were studied. The bone mineral concentration (BMC) and BMD were assessed at lumbar spine, distal radius, and neck of femur. Biochemical parameters like serum calcium and vitamin D levels were also assessed. Results. The BMC of neck of femur was significantly low in cases in comparison to controls. We also observed significantly lower BMD at the lumbar spine in cases in comparison to controls. A significantly positive correlation was observed between serum calcium levels and BMD at neck of femur. Conclusion. Hence, low serum calcium may be used as a predictor of low BMD especially in populations where incidence of hypovitaminosis D is very high.